A microfluidics-integrated impedance/surface acoustic resonance tandem sensor - Kustanovich, Kiryl; Yantchev, Ventsislav; Doosti, Baharan Ali; Gözen, Irep; Jesorka, Aldo (Sensing and Bio-Sensing Research, 2019)
We demonstrate a dual sensor concept for lab-on-a-chip in-liquid sensing through integration of surface acoustic wave resonance (SAR) sensing with electrochemical impedance spectroscopy (EIS) in a single device. In this concept, the EIS is integrated within the building blocks of the SAR sensor, but features a separate electrical port. The two-port sensor was designed, fabricated, and embedded in a soft polymer microfluidic delivery system, and subsequently characterized. The SAR-EIS tandem sensor features low cross-talk between SAR and EIS ports, thus promoting non-interfering gravimetric and impedimetric measurements. The EIS was characterized by means of the modified Randle's cell lumped element model. Four sensitive parameters could be established from the tandem sensor readout, and subsequently employed in a proof of principle study of liposome layers and their interaction with Ca2+ ions, leading to transformation into molecular film structures. The associated shift of the sensing quantities is analysed and discussed. The combination of impedimetric and gravimetric sensing quantities provides a unique and detailed description of physicochemical surface phenomena as compared to a single mode sensing routine.